Interchangeability of Assistants in The Meaning of Time (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article is about the exchange of postpositions in the sense of time. The study of the synonymous relationship of time-sense facilitators is used in comparative research with other linguistic units.